2010
DOI: 10.5194/cp-6-575-2010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of brine-induced stratification on the glacial carbon cycle

Abstract: Abstract. During the cold period of the Last Glacial Maximum (LGM, about 21 000 years ago) atmospheric CO 2 was around 190 ppm, much lower than the pre-industrial concentration of 280 ppm. The causes of this substantial drop remain partially unresolved, despite intense research. Understanding the origin of reduced atmospheric CO 2 during glacial times is crucial to comprehend the evolution of the different carbon reservoirs within the Earth system (atmosphere, terrestrial biosphere and ocean). In this context,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 56 publications
(99 reference statements)
4
107
0
1
Order By: Relevance
“…This mechanism was shown to result in a net glacial CO 2 decrease. Previous studies also showed that frac = 0.6 is a good estimate (Bouttes et al, 2010(Bouttes et al, , 2011. In this study the frac parameter is thus set to 0.6 when the sinking of brines is taken into account.…”
Section: Sinking Of Brines In Climber-2mentioning
confidence: 99%
See 4 more Smart Citations
“…This mechanism was shown to result in a net glacial CO 2 decrease. Previous studies also showed that frac = 0.6 is a good estimate (Bouttes et al, 2010(Bouttes et al, , 2011. In this study the frac parameter is thus set to 0.6 when the sinking of brines is taken into account.…”
Section: Sinking Of Brines In Climber-2mentioning
confidence: 99%
“…1c). We then explore the impact of the same fresh water fluxes in a situation with more realistic glacial CO 2 levels obtained including the "brine sinking" mechanism previously studied (Bouttes et al, 2010(Bouttes et al, , 2011. Finally, we evaluate the impact of adding fresh water flux to the Southern Ocean.…”
Section: N Bouttes Et Al: Fresh Water Fluxes Impact On the Carbon Cmentioning
confidence: 99%
See 3 more Smart Citations